Hubungan Dukungan Sosial dan Fasilitas Latihan terhadap Motivasi Belajar Mahasiswa Porkes pada Mata Kuliah Tenis Lapangan - Fathan Arisyi, Muhammad; Muhammad Ali; Wawan Junresti Daya; Ilham; Ugi Nugraha; Reza Hadinata; Alek Oktadinata; Endarman Saputra (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the relationship between social support and training facilities on students’ learning motivation in the Sports and Health Education Study Program (PORKES) in tennis courses. This research employed a quantitative approach with a correlational design. The population consisted of 155 students using total sampling technique. Data were collected using validated questionnaires and analyzed using Pearson correlation and multiple linear regression. The results showed that social support (r = 0.089; p > 0.05) and training facilities (r = 0.079; p > 0.05) had a positive but very weak and non-significant relationship with learning motivation. Regression analysis also indicated that social support (p = 0.379) and training facilities (p = 0.474) did not significantly influence learning motivation. The study's conclusions indicate that social support and training facilities do not significantly influence learning motivation, suggesting that other factors beyond the studied variables may influence student learning motivation. Therefore, a more comprehensive learning strategy is needed to improve student learning motivation. Keywords: Learning Motivation, PORKES Students, Social Support, Tennis Court, Training Facilities.